Development and characterization of photoprotective nanoemulsions containing Babassu (Orbignya phalerata Mart.) lipophilic extract - Italo Rennan Sousa Vieira; Ana Clara Lima Nunes Silva; Natalia Ruben Castro; Cristal dos Santos Cerqueira Pinto; Zaida Maria Faria de Freitas; Eduardo Ricci-Júnior; Elisabete Pereira dos Santos; Adriana Leandro Camara; Maria Célia Pires Costa; Carlos Adam Conte-Junior (Universidade de São Paulo, 2023)
Abstract Oil-in-water photoprotective nanoemulsions (NEs) were developed using Babassu (BBS) lipophilic extract, nonionic surfactants, and low concentrations of organic sunscreens by ultrasonic processing. BBS extract was chosen due to its suitable physicochemical properties (acidity index, peroxide index, refraction index, and relative density) and predominance of saturated fatty acids, identified by gas chromatography-mass spectrometry (GC-MS), which promote biological activities and high oxidative stability. NEs were characterized by mean droplet size, morphology, polydispersity index (PdI), pH, and organoleptic properties, and the physical stability of the NEs was evaluated for 120 days at room temperature. The sun protection factor (SPF) was determined, and the photostability and in vitro cytotoxicity assays were performed for NEs. All NEs remained stable for 120 days, with a droplet size <150 nm and a monomodal distribution profile. The pH values were compatible with the skin's pH. NE3 showed a spherical morphology, with a mean droplet size of 125.15 ± 0.16 nm and PdI of 0.145 ± 0.032. NE3 containing BBS extract and sunscreens presented an SPF of 35.5 ± 3.0, was photostable after 6 h of radiation and was non-cytotoxic to fibroblast cells. Thus, NE3 could be considered a promising formulation for developing synergic plant-extract sunscreen photoprotective products for the market.